Difficulties in diagnosing colorectal cancer with ovarian metastasis: a literature review (Research, Society and Development, 2021)
The process in which colorectal cancer (CRC) is metastasized to the ovary remains unclear. However, it is considered that, as there is no lymphatic flow between the colon and the ovaries, both hematogenous and disseminated peritoneal metastases present possible metastatic pathways. This study has as objective to describe the difficulties and how the diagnosis of colorectal cancer with ovarian metastasis is done. This work was carried out through the Virtual Health Library (VHL) at Pubmed and Medline databases, using the crossings of the descriptors in English “Colorectal cancer”, “Ovarian metastasis”, and “Diagnosis”. To evaluate the research problem and its stratification, it was used the PVO strategy, which can be seen in Table 1. Such strategy permitted the formulation of the following guiding question: “How is the diagnosis of colorectal cancer with ovarian metastasis done?”. Differential diagnosis between primary tumors and ovarian metastases is often difficult. Symptoms associated with the development of ovarian cancer can hide an intestinal disease. Serum values of carbohydrate antigen tumor markers (CA-125) and carcinoembryonic antigen (CEA) have an important role in differentiating patients with primary CRC with ovarian metastasis. Although difficult, the differential diagnosis must be done early to minimize complications. Diagnostic alternatives include histopathological evaluation with the identification of metastatic histological subtypes similar to primary colorectal cancer subtypes, being mucinous adenocarcinoma the most common.